Astrotheology: The natural interface between hyperspace and the Trinity - A.C. Pieterse (Acta Theologica)
Over the past few decades, physicists are seeking a unifying theory that could encapsulate the theories of general relativity and quantum mechanics, our understanding of the very big and the infinitesimal small, into one all-inclusive theory. This quest led to a renewed interest in the proposal of hyperspace, which states that the structure of space and time are folded into one another, creating multiple dimensions. The author believes that the biblical confession about the resurrected Christ could be beneficial to science and theology in this respect. Biblical testimony provides insight into the apparent natural and effortless movement of Christ between the different dimensions in nature. Astrotheology, as a nexus between the different disciplines, is well equipped to describe themeaning and implications of the resurrection with regard to the fabric of space-time. The author opines that it could facilitate as a natural interface between hyperspace and the Trinity. This proposal aims to accentuate, from a scriptural point of view, that reality indeed comprises more than four dimensions and that astrotheology could make a significant epistemological contribution in the dialogue about hyperspace and God’s agency in creation.